IMPACT OF COVID-19 ON RUPIAH EXCHANGE RATE MOVEMENT AGAINSTUS DOLLARS AND COMPOSITE STOCK PRICE INDEX IN INDONESIA - Irwan Moridu (Politeknik Negeri Batam, 2022)
The purpose of this study is to analyze the impact of Covid-19 in the Rupiah Exchange Rate on the United States Dollar and the Composite Stock Price Index in Indonesia. The data used are primary and secondary data: the Rupiah Exchange Rate and the CSPI value taken for 66 days starting from October 2019 to March 2020. The data were analyzed descriptively by explaining the impact caused by Covid-19. The results found that the Covid-19 Pandemic harmed the economy both the Rupiah Exchange Rate against the US Dollar and the movement of the Composite Stock Price Index in Indonesia. The findings found that before the Covid-19 Pandemic the value of the Rupiah against the US Dollar and the movement of the Composite Stock Price Index experienced negative sentiment while after the Covid-19 pandemic it moved negatively due to negative sentiment from market participants who were still focused on the spread of the Covid-19 pandemic in Indonesia, as well as many market players who still sell shares because of global panic. Nevertheless, the Indonesian government has anticipated the economic downturn in Indonesia by implementing fiscal policies, to reduce the negative impact of the Covid-19 pandemic.